A 3‐Pyridyl‐5, 15‐Diazaporphyrin Nickel(II) Complex as a Bidentate Metalloligand for Transition Metals1. Issue 50 (22nd October 2014) - Yamaji, Ayaka; Shin, Ji‐Young; Miyake, Yoshihiro; Shinokubo, Hiroshi
Abstract 3‐Pyridyl‐5, 15‐diazaporphyrin nickel(II) serves as a bidentate metalloligand for platinum(II), ruthenium(II), and rhenium(I) metal centers. Single‐crystal X‐ray diffraction analysis of these metal complexes unambiguously reveals the presence of a dative bond between the outer metal center and the meso‐nitrogen atom. The UV/Vis absorption spectra of the complexes show substantially red‐shifted bands which are perturbed by outer‐metal coordination. This is due to the contribution of metal‐to‐ligand charge transfer interactions.